GAMBARAN HIGIENE SANITASI PENYELENGGARAAN MAKANAN DAN KEBERADAAN BAKTERI Escherichia coli PADA PERALATAN MAKAN DI LINGKUNGAN KANTIN UNIVERSITAS SUMATERA UTARA TAHUN 2015 - rifhan dita; indra chahaya; surya dharma (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Hygiene of Food equipment have a important role in growth and spread of the pathogenic organism. Food equipment must be maintained to avoid the contamination of germs such as Escherichia coli. The aim of this study was to analyze the hygiene sanitation condition of food processing and examination of Escherichia coli bacteria in food equipment in the cafeteria University of Sumatera Utara 2015.This study is a quantitative research . The study was conducted in 16 cafeteria at the University of Sumatera Utara. This study uses observation sheets to see the hygiene and sanitation of food and laboratory testing for the presence of Escherichia coli bacteria that will be meet with regulation in Kepmenkes No. 1098 / Menkes / SK / VII / 2003 The result of this research found conditions of hygiene and sanitation of food processing based on physical conditions of the location and the building, as well as the six principles of hygiene sanitation food was good but in terms of canteen facilities, the condition of the kitchen, dining room, and the building of foodstuffs as well as in the provision of food equipment to eat is still relatively poorly , There were 8 canteen that contained the bacteria Escherichia coli. It is recommended that food seller in University of Sumatera Utara should pay more attention canteen facilities, the condition of the kitchen, dining room, and building materials as well as in the provision of food equipment eat. The city health office Medan should conduct surveillance and health promotion regarding hygiene sanitation in the cafeteria University of Sumatera Utara Keywords: Sanitation, Hygiene, Tableware, Escherichia coli